2010
DOI: 10.2353/ajpath.2010.100552
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Neurites Containing C-Terminally Truncated α-Synuclein Are Present in Alzheimer's Disease without Conventional Lewy Body Pathology

Abstract: The pathological hallmark of Parkinson's disease and diffuse Lewy body disease (DLBD) is the aggregation of ␣-synuclein (␣-syn) in the form of Lewy bodies and Lewy neurites. Patients with both Alzheimer's disease (AD) and cortical Lewy pathology represent the Lewy body variant of AD (LBV) and constitute 25% of AD cases. C-terminally truncated forms of ␣-syn enhance the aggregation of ␣-syn in vitro. To investigate the presence of C-terminally truncated ␣-syn in DLBD, AD, and LBV, we generated and validated pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 38 publications
3
39
0
4
Order By: Relevance
“…Furthermore, C-terminally truncated aSyn is ubiquitously present in Lewy bodies of PD brains, and the amount of truncated forms is correlated with the number and size of Lewy bodies (18,19), suggesting that truncation of aSyn might be an early event that renders it more prone to aggregate into disease-associated conformations. A number of in vitro studies have investigated this possibility and have implicated different proteases that theoretically could truncate aSyn, including neurosin (20), 20S proteasome (21,22), calpain-1 (23), matrix metallo-proteases (MMPs) (24), and cathepsin D (25). However, these are general proteases that cleave proteins, including aSyn, at multiple locations, and some are extracellular proteases (i.e., neurosin and MMPs); therefore, their roles in truncating aSyn intracellularly in vivo remain unclear.…”
Section: Significancementioning
confidence: 99%
“…Furthermore, C-terminally truncated aSyn is ubiquitously present in Lewy bodies of PD brains, and the amount of truncated forms is correlated with the number and size of Lewy bodies (18,19), suggesting that truncation of aSyn might be an early event that renders it more prone to aggregate into disease-associated conformations. A number of in vitro studies have investigated this possibility and have implicated different proteases that theoretically could truncate aSyn, including neurosin (20), 20S proteasome (21,22), calpain-1 (23), matrix metallo-proteases (MMPs) (24), and cathepsin D (25). However, these are general proteases that cleave proteins, including aSyn, at multiple locations, and some are extracellular proteases (i.e., neurosin and MMPs); therefore, their roles in truncating aSyn intracellularly in vivo remain unclear.…”
Section: Significancementioning
confidence: 99%
“…5 One study also found that a high proportion of abnormal neurites containing a form of α-synuclein, as in DLB, may also be found in AD, without the conventional Lewy body pathology. 43 However, the neurites in DLB are far more likely to be α-synuclein immunoreactive rather than tau immunoreactive as in AD, and other features of AD pathology such as neurofibrillary tangles are rarely seen in DLB. 44 These findings suggest that DLB and AD may simply be points along a spectrum of a more general neurodegenerative disorder and there may even be a variant of dementia between DLB and AD, the 'Lewy body variant of Alzheimer's disease'.…”
Section: Neuropathologymentioning
confidence: 99%
“…Up to 6 0 % o f A D c a s e s e x h i b i t s i g n i f i c a n t synucleinopathology in addition to plaques and tangles (Hamilton 2000). An increasing body of evidence suggests that over-expression and aggregation of α-synuclein may play pathogenic roles in synaptic dysfunction, cytotoxicity, and AD (Lewis et al 2010). In our previous study, we reported that α-synuclein mRNA and protein expression were increased in a time-dependent manner in the hippocampus of APPV717I transgenic mice at the ages of 4, 10, and 16 months, and α-synuclein aggregation occurred at the age of 16 months .…”
Section: Introductionmentioning
confidence: 99%